How much multilateralism do we need? Effectiveness of unilateral agricultural mitigation efforts in the global context. (8th October 2021) - Frank, Stefan; Havlík, Petr; Tabeau, Andrzej; Witzke, Peter; Boere, Esther; Bogonos, Mariia; Deppermann, Andre; van Dijk, Michiel; Höglund-Isaksson, Lena; Janssens, Charlotte; Kesting, Monika; van Meijl, Hans; et al.
Abstract: Achieving climate neutrality in the European Union (EU) by 2050 will require substantial efforts across all economic sectors, including agriculture. At the same time, an ambitious unilateral EU agricultural mitigation policy is likely to have adverse effects on the sector and may have limited efficiency at global scale due to emission leakage to non-EU regions. To analyse the competitiveness of the EU's agricultural sector and potential non-CO2 emission leakage conditional on mitigation efforts outside the EU, we apply three economic agricultural sector models. We find that an ambitious unilateral EU mitigation policy in line with efforts needed to achieve the 1.5 °C target globally strongly affects EU ruminant production and trade balance. However, since EU farmers rank among the most greenhouse gas efficient producers worldwide, if the rest of the world were to start pursuing agricultural mitigation efforts too, economic impacts of an ambitious domestic mitigation policy get buffered and EU livestock producers could even start to benefit from a globally coordinated mitigation policy.